Mating Strategy in the Arab Horse Population Over 30 Years in Algeria - Benia Ahmed R.; Benamor Naceur; Bounaceur Farid; Belalia Abdelkader; Petit Daniel (Acta Veterinaria)
The objective of this research was to describe the variation in breeding practices in the population of Arabian horses in Algeria in relation to the population size drop observed in the 2000s, due to an increase in the cost of food and a change in interest in racing, related to the black decade. As a result, the breeders had to face two opposite constraints: enhancing reproduction to counter the population decline and preventing the loss of genetic diversity. The aim of the study was to evaluate the genetic consequences of the decisions taken over a period of 30 years, starting from 1988 to 2018. The study was based on the analyses of the stud-book and on 11 microsatellite markers in a group of 943 horses, distributed into 13 age classes. Between 2004 and 2008, the breeders purchased foreign sires and dams, allowing a relative stability in unbiased heterozygosity of about 71%, due to the high genetic distances between foreign and local horses. As these importations stopped from 2009 on, there was a decrease in allele numbers of about 20%. Moreover, from 2010 on, we observe an excess of inbreeding and an increase in genetic drift relative to the starting population, due to population size decline. From the analysis of genetic distances between local individuals, it seems that the only constraint for sires and dams allowed to mate was a null coefficient of inbreeding.